Luther on women: a sourcebook - Karant-Nunn, Susan C.; Wiesner, Merry E. (Cambridge University Press, 2003)
Martin Luther contributed extensively to the sixteenth century 'debate about women' with his writings on women and related subjects such as marriage, the family and sexuality. In this volume, Merry Wiesner-Hanks and Susan Karant-Nunn bring together a vast selection of these works, translating many into English for the first time. They include sermons, lectures, pamphlets, polemic writings, letters and some informal 'table talk' recorded by his followers. The book is arranged into chapters on Biblical women, marriage, sexuality, childbirth and witchcraft, as well as on Luther's relations with his wife and other contemporary women. The editors, both internationally-known scholars on Reformation and women, provide a general introduction to each chapter, and Luther's own colourful words fuel both sides of the debate about whether the Protestant Reformation was beneficial or detrimental to women. This collection will make a wide range of Luther's works accessible to English-speaking scholars, students and general readers.